2018
DOI: 10.15414/jmbfs.2018.8.2.774-780
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dye Degrading Potential of Suspended and Nanoparticle Immobilized Cells of Pseudomonas Aeruginosa Ar-7

Abstract: The commercial use and unrestricted disposal of synthetic dyes in soil and water-bodies, following the industrial revolution, has led to a major threat towards environmental safety. The azo-dye, Remazol Black B (RBB) is one of the most commonly used synthetic reactive dyes in textile industries. In the present study, the decolourization and biodegradation of RBB were investigated using a bacterium isolated from the marine environment, which was later identified as Pseudomonas aeruginosa AR-7 by 16S rRNA analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…The results in the current study were similar to those of Surti and Ansari [ 54 ] who found that the GC–MS analysis of metabolites extracted from the MSM broth altered with 0.5-mL dye wastewater showed complete degradation of dye, as indicated by the comparison between GC–MS chromatogram of pure and degraded dyes. Jamil et al [ 70 ] also found that the GC–MS analysis indicates the complete breakdown of disperse violet 26 into inorganic compounds and ions of low molecular weight, for example, H 2 O, CO 2 , NO 3 , etc.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results in the current study were similar to those of Surti and Ansari [ 54 ] who found that the GC–MS analysis of metabolites extracted from the MSM broth altered with 0.5-mL dye wastewater showed complete degradation of dye, as indicated by the comparison between GC–MS chromatogram of pure and degraded dyes. Jamil et al [ 70 ] also found that the GC–MS analysis indicates the complete breakdown of disperse violet 26 into inorganic compounds and ions of low molecular weight, for example, H 2 O, CO 2 , NO 3 , etc.…”
Section: Resultssupporting
confidence: 90%
“…This might be attributed to the differences in electron distribution, charge density, or steric factors [ 19 ]. Consistent with this study, the maximum decolorization percentages of Remazol Black B were achieved in the presence of glucose (87.5%) and yeast extract (83.3%) from treatment with Pseudomonas aeruginosa [ 54 ]. Carbon and nitrogen sources were used to enhance enzyme production because they contain essential minerals and nutrients to be used as energy for growth [ 19 ].…”
Section: Resultssupporting
confidence: 75%